Thoughts on Cord Knotting as an Early Record-Keeping System in Ancient China - Szigethy, Balázs (Távol-keleti Tanulmányok, 2026)
Is it possible to demonstrate the existence of cord knotting in ancient China, and if so, how might it have influenced the evolution of the Chinese writing system? In this paper I am aiming to examine the existence of cord knotting in ancient China and its potential influence on the evolution of Chinese writing. By reviewing extant Chinese scholarship and comparing cord knotting practices with similar mnemonic and accounting devices worldwide, I propose that although cord knotting predates Chinese writing, it did not directly lead to its development; rather, it evolved contemporaneously as an independent system of record keeping, that later contributed stylistic elements to the formation of Chinese characters. Cord knotting served as a mnemonic tool for recording labour days, wages, loans, and other vital economic transactions, and its visual conventions may have contributed to the formation of the silk classifier found in many Chinese characters. This study situates cord knotting within broader global practices while reevaluating traditional Chinese texts, suggesting that the aesthetic and functional elements of knotted cords played a significant role in the emergence and evolution of Chinese logographs. Building on this claim, the paper develops three lines of argument. First, it establishes a global comparative baseline for ‘rope media’ by synthesizing Cyrus L. Day’s tripartite typology—magical/apotropaic, mnemonic (numerical and cultural), and practical knots—and by reviewing rich cross-cultural cases such as the Andean khipu, Polynesian and North American mnemonic cords, Hawaiian ‘tax-gatherer’s memorandum cords’, and the Ryukyuan warazan straw-cord counting system. These analogues demonstrate that knot-based records can sustain durable administrative functions—time-reckoning, tribute accounting, genealogical recall—without becoming phonographic writing. They therefore provide a plausible technological ecology within which a Chinese cord-record system could have coexisted with, but remained distinct from, early script. The study re-examines Chinese classical references to cord knotting (Yi·xici, Shuowen postface, Zheng Xuan’s commentaries, Wenxin diaolong, Zhuangzi, and ethnographic notices) not as direct proof but as cultural memory of an administrative practice. To avoid what I call ‘textual primacy bias’, these sources are balanced against palaeographic and archaeological evidence. Applying Demattè’s criteria for identifying precursors to Shang script, the paper concludes that cord knotting does not qualify as writing in the strict sense, functioning instead as a mnemonic aid for counting and verification. Claims that rope impressions, such as those at Dadiwan, represent archives of records are re-evaluated and more plausibly interpreted as constructional remains, though they still confirm rope’s availability in the Neolithic. At the same time, a narrower stylistic influence is proposed in line with Keightley’s ‘visual pun’ model, whereby script signs schematize familiar tools and practices. Early forms of 糸 and related graphs (叀, 專, 傳) may encode the cord, the knot, the knot-keeper, and the act of transmission. Other graphs tied to numbers, contracts, and genealogy (e.g., 廿, 卅, 卌, 貰, 貸, 世, 孫) plausibly echo domains where knot records were used—tallying, valuing, and marking descent. This does not imply a linear derivation of writing from cords, but rather that knotting culture provided visual and conceptual resources for scribes. Cord knotting is therefore best understood as a parallel technology that was eventually supplanted by graphemic writing, yet left stylistic fingerprints in early Chinese script, particularly within silk-classifier graphs and administrative vocabulary. While perishable materials make direct proof unlikely, archaeological preconditions—rope production, counting needs, and social complexity—support the plausibility of such systems. In this light, writing in China developed independently but might have absorbed aspects of cord knotting’s visual and semantic logic.